2021
DOI: 10.1186/s13148-020-00996-1
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis reveals the alterations that LMNA interacts with euchromatin in LMNA mutation-associated dilated cardiomyopathy

Abstract: Background Dilated cardiomyopathy (DCM) is a serious cardiac heterogeneous pathological disease, which may be caused by mutations in the LMNA gene. Lamins interact with not only lamina-associated domains (LADs) but also euchromatin by alone or associates with the lamina-associated polypeptide 2 alpha (LAP2α). Numerous studies have documented that LMNA regulates gene expression by interacting with LADs in heterochromatin. However, the role of LMNA in regulating euchromatin in DCM is poorly under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 48 publications
(33 reference statements)
2
7
0
Order By: Relevance
“…In addition, cytokine–cytokine receptor interaction and chemokine‐mediated signaling pathways were differentially regulated. Intriguingly, this is consistent with the previous DCM‐associated transcriptome studies (Liu et al., 2021; Zhang et al., 2021). However, genes from the most strongly affected signaling pathways (IL‐17 signaling and cytokine production) were downregulated in the mutant, whereas most clinical investigations have reported elevated cytokine levels in cardiomyopathy patients (Gerbino et al., 2021).…”
Section: Resultssupporting
confidence: 92%
“…In addition, cytokine–cytokine receptor interaction and chemokine‐mediated signaling pathways were differentially regulated. Intriguingly, this is consistent with the previous DCM‐associated transcriptome studies (Liu et al., 2021; Zhang et al., 2021). However, genes from the most strongly affected signaling pathways (IL‐17 signaling and cytokine production) were downregulated in the mutant, whereas most clinical investigations have reported elevated cytokine levels in cardiomyopathy patients (Gerbino et al., 2021).…”
Section: Resultssupporting
confidence: 92%
“…Both the Chromotek beads as well as the p SB- co -(aGFP) 8% beads were able to capture the three core subunits of the PRC2 complex: EED, EZH2, and SUZ12, as well as all of the other previously identified binding partners by Smits et al that occur at >0.1 stoichiometry relative to the EED bait protein: RBBP47, EZH1, JARID2, C17orf96, AEBP2, and PCL23 (Figure , green dots and labels). , With the p SB- co -(aGFP) 8% beads, three additional proteins scored just positive: LMNA, HIST1H4A, and HIST1H2BL (Figure , yellow dots and labels). The LMNA protein is, like the PRC2 complex, a chromatin regulator, , and was previously shown to also interact with one another. , The RBBP4/7 proteins operate in several protein complexes and can bind to histone H4, whereas ABP2 and JARID2 can bind to histone 2 . The PRC2 complex, the histone proteins and the LMNA proteins are thus found in close proximity to each other within the cell nucleus, and the LMNA, HIST1H4A, and HIST1H2BL proteins might in fact reflect true protein–protein interactors with the PRC2 complex (hence the labeling of these proteins in yellow).…”
Section: Resultsmentioning
confidence: 97%
“…9,49 With the pSB-co-(aGFP) 8% beads, three additional proteins scored just positive: LMNA, HIST1H4A, and HIST1H2BL (Figure 6, yellow dots and labels). The LMNA protein is, like the PRC2 complex, a chromatin regulator, 49,53 and was previously shown to also interact with one another. 54,55 The RBBP4/7 proteins operate in several protein complexes and can bind to histone H4, 56 whereas ABP2 and JARID2 can bind to histone 2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A-type lamins are mostly located at the nuclear periphery and bind LADs but a pool of these proteins can be associated with the open chromatin (euchromatin) (Gesson et al, 2014). Recently, two studies have shown an alteration of A-type lamins interaction with euchromatin in dilated cardiomyopathy (Zhang et al, 2021;Feng et al, 2022). Collectively, all these studies participate to understand the underlying mechanisms of the disease pathogenesis.…”
Section: Chromatin Reorganization In Cardiolaminopathymentioning
confidence: 99%